Exercise Intervention in Autonomic Function, Immunity, and Cardiovascular Health: A Precision Medicine Approach - Jianyu Li; Junbei Bai; Guochun Liu; Ziyan Zhu; Chunmei Cao (Journal of Cardiovascular Development and Disease, 2025)
The imbalance in the interaction between the autonomic nervous system and the immune system serves as a central mechanism in the onset and progression of cardiovascular diseases. The excessive activation of the sympathetic nervous system and suppression of vagal function contribute to chronic inflammation and cardiac remodeling. Precision medicine, by integrating multidimensional data such as genomics and metabolomics, offers a novel perspective for the personalized design of exercise interventions. This systematic review explores the bidirectional regulatory mechanisms of exercise interventions on the autonomic nervous system–immune axis and examines the potential applications of precision medicine in optimizing exercise prescriptions and clinical translation. Exercise significantly improves cardiovascular function through immunometabolic reprogramming, which includes suppressing sympathetic overactivity, enhancing vagal tone, and modulating the IL-6/IL-10 balance, as well as activating the short-chain fatty acid (SCFA)–Treg axis. Moreover, precision-medicine-driven ACE I/D gene typing provides a basis for selecting tailored exercise prescriptions, thereby significantly enhancing the efficacy of exercise interventions. By leveraging a multi-tiered “neuro–immune–metabolic” regulatory framework, exercise interventions contribute to improved cardiovascular health. The application of precision medicine technology overcomes individual variability constraints, advancing exercise prescription design from generalized recommendations toward personalized and dynamically adaptive strategies.